Specific Characteristics of using Chinese Experience for Poverty Reduction in Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article describes the causes, main trends and ways of reducing poverty in Uzbekistan, as well as information on the effectiveness of using the experience of the Chinese state.